Racial Disparities in Emergency Department Utilization for Dental/Oral Health-Related Conditions in Maryland - Chalmers, Natalia I. (Frontiers in Public Health, 2017)
Objectives: The hospital emergency departments (EDs) are a place where many Americans seek treatment of dental conditions. Racial and ethnic minorities have consistently higher rates than whites of ED utilization for dental conditions. The reasons for these disparities and significant public health concerns are investigated less often. In this paper, we measure trends in racial disparities in ED discharges for dental conditions in Maryland from 2010 to 2013. To understand these disparities, we also describe differences between racial groups in age, gender, income, location, payer, comorbidities, and the availability of dental care. Methods: 2010-2013 State Emergency Department Data (SEDD) for Maryland was used in the analysis. Rates per 100,000 of the population are calculated using information from Census Population Estimates. Cost-to-Charge ratios are used to estimate the costs of ED discharges. Dental/Oral Health Related Conditions (DOHRC) are defined as discharge diagnoses of ICD-9-CM codes 520.0 through 529.9. Descriptive statistics and fixed effects logistic regression models with a rare event correction are used to analyze the data. Results: Blacks, especially females ages 25-34, have larger proportions of total ED discharges due to DOHRC, and higher population rates of DOHRC than any other racial or ethnic group. In 2013, Blacks represented 30% of Maryland’s population and accounted for 52% of ED costs for DOHRC. Hispanics and those of other races have much lower rates of DOHRC discharges. The regression results show that the high proportion of DOHRC discharges among Blacks may be explained by the concentration of Blacks in low-income central cities with less access to dental care. Conclusion: There are significant racial disparities in the emergency department utilization for dental/oral health related conditions in Maryland. These disparities reflect the lack of access to dental care, due to both cost and geographic limitations. This results in high healthcare costs and ineffective solutions for patients. Addressing oral health disparities will require policy solutions that are targeted to the populations most at need, and action plans that combine community and state level efforts.